ISU TERORISME DAN RESPONS AKTIVIS MUDA ACEH - Amiruddin, M. Hasbi (WALISONGO, 2014)
This article wants to examine the extent of radical thought in the minds of theyounger generation pervasive in Aceh. With the new Aceh conditions experiencedseveral years of post-conflict situation safe again struck by discovered a number ofterrorists who make Jalin mountains forest, Aceh Besar, as a military trainingground. Also found are also a number of books that have a narrative that can bringinspiration radicalism and terrorism acts. The results of in-depth interviews ofyoung activists in Aceh, can be explained that the concept of terrorism modelsstruggle can not be accepted by young activists in the city of Banda Aceh. Theyhave to understand the teachings of Islam that is relatively comprehensive andproportional. But their ideals in order to uphold Islamic shariah in Aceh is anecessity.Artikel ini ingin melihat sejauhmana pemikiran radikal merasuk dalam pikirangenerasi muda di Aceh. Dengan kondisi Aceh yang baru beberapa tahun mengalamisituasi aman pasca terjadi konflik kembali dikejutkan dengan ditemukansejumlah teroris yang menjadikan hutan pegunungan Jalin, Aceh Besar, sebagaimedan latihan militer. Selain itu ditemukan juga sejumlah buku-buku yangmemiliki narasi yang dapat memunculkan inspirasi tindakan radikalisme danterorisme. Hasil wawancara mendalam terhadap para aktivis muda Aceh, dapatdijelaskan bahwa konsep perjuangan model terorisme tidak dapat diterima olehaktivis muda di Kota Banda Aceh. Mereka telah memahami ajaran Islam yangrelatif komprehensif dan proporsional. Namun cita-cita mereka agar tegaknyasyariat Islam di Aceh adalah suatu keniscayaan.